In an arithmetic sequence, the \( n \)-th term can be expressed using the formula:
\[ a_n = a_1 + (n - 1) d \]
where \( a_n \) is the \( n \)-th term, \( a_1 \) is the first term, \( d \) is the common difference, and \( n \) is the term number.
Given:
- \( a_{38} = -5 \)
- \( d = -2.9 \)
- \( n = 38 \)
We can plug these values into the formula to find \( a_1 \):
\[ -5 = a_1 + (38 - 1)(-2.9) \]
This simplifies to:
\[ -5 = a_1 + 37(-2.9) \] \[ -5 = a_1 - 107.3 \]
Now, solving for \( a_1 \):
\[ a_1 = -5 + 107.3 \] \[ a_1 = 102.3 \]
Thus, the first term of the arithmetic sequence is:
\[ \boxed{102.3} \]